2005
DOI: 10.5713/ajas.2005.1242
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Ability of Bovine Embryos Nuclear Transferred with Frozen-thawed or Cooled Donor Cells

Abstract: This study was designed to investigate the in vitro developmental ability and apoptosis of bovine embryos nucleartransferred (NT) with frozen-thawed or cooled donor cells. Cultured adult bovine ear cells were used as donor cells after sub-culturing to confluence (CC), cooling to 4°C for 48 h, or freezing-thawing (FT). Apoptotic cells in blastocysts were evaluated for apoptosis by terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) method. Fusion, cleavage and blastocyst rates were 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Most cell banks emphasize conservation and utilization of animal resources, in particular animal generative cells and embryos (Ho et al 1997;Oishi 1997;Simon 1999;Park et al 2009). In addition to these methods, the development of modern somatic cell cloning techniques has made somatic cells an attractive resource for the conservation of animal genetic materials (Wu 1999;Hong et al 2005;Yun et al 2008). There have been a number of recent publications on the development of fibroblast cell lines from various animals, including the Debao pony (Ma et al 2004), Beijing fatty chicken , sheep (Chen et al 2006), Taihu pig , Luxi cattle , and white ear lobe chicken (Wu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most cell banks emphasize conservation and utilization of animal resources, in particular animal generative cells and embryos (Ho et al 1997;Oishi 1997;Simon 1999;Park et al 2009). In addition to these methods, the development of modern somatic cell cloning techniques has made somatic cells an attractive resource for the conservation of animal genetic materials (Wu 1999;Hong et al 2005;Yun et al 2008). There have been a number of recent publications on the development of fibroblast cell lines from various animals, including the Debao pony (Ma et al 2004), Beijing fatty chicken , sheep (Chen et al 2006), Taihu pig , Luxi cattle , and white ear lobe chicken (Wu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the BL formation of NT embryos is extremely variable. The percentage of nuclear transfer embryos developing to blastocyst stage ranges from less than 5% to greater than 65% (Hills et al, 2000;Kubota et al, 2000;Dong et al, 2004;Hong et al, 2005). Recent studies of SCNT-derived embryos have shown that a high proportion of embryos contain cells with abnormal chromosome numbers from 0% to 75% (Mohamed and Takahashi, 2000;Arat et al, 2002;Booth et al, 2003;Slimane-Bureau et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study was designed to evaluate whether morphological selection of embryos based on cell number on Day 2 of in vitro culture (IVC) could offer a practical and valuable non-invasive means to select good quality porcine embryos produced by SCNT or parthenogenesis. Parthenogenetic embryos were chosen as the control instead of in vitro fertilized (IVF) embryos because we and others have earlier shown that development characteristics of parthenogenetic embryos resembled those of IVF and SCNT embryos (Kure-bayashi et al, 2000;Hong et al, 2005;Gupta et al, 2007a;Gupta et al, 2008a;. Moreover, contrary to IVF embryos, use of parthenogenetic embryos avoids the confounding variation due to influence of male/sperm factor and polyspermy which is particularly common in porcine species (Han et al, 1999).…”
Section: Introductionmentioning
confidence: 99%